Passive Optical Networks Progress: A Tutorial - Tomas Horvath (Electronics, 2020)
For many years, passive optical networks (PONs) have received a considerable amount of attraction regarding their potential for providing broadband connectivity to almost every citizen, especially in remote areas where fiber optics can attract people to populate regions that have been abandoned. Error-free connectivity without dropouts can offer new opportunities to communicate, earn money and enjoy cultural events. Transmission speeds are multigigabit with distances of a few tens of kilometers; these specifications were previously reserved for high-speed and long-haul backbone networks. PONs can also support a new class of applications, such as accurate time transfer or distributed fiber sensing and follow new trends in open networking. An outline of past and current standards and standards that have been proposed for the latest generation of multigigabit PONs is provided.